Metal toxicity and environmental effects on health: a study report on mineral and heavy metal contents of different Malaysian fish species - Octavianti, Fitri; Jaswir, Irwandi (Faculty of Food Science & Technology, Universiti Putra Malaysia (UPM), 2017)
Abstract: This paper discusses effects of metal toxicity and environmental on health and followed by a study report on mineral and heavy metal contents of fish conducted in Malaysia as an example. Fish, a part of being a good source of digestible protein vitamins, minerals and polyunsaturated fatty acids (PUFAs), are also an important source of heavy metals. Some of the metals found in the fish might be essential as they play important role in biological system of the fish as well as in human being, some of them may also be toxic as might cause a serious damage in human health even in trace amount at certain limit. A comprehensive study was conducted to fishes collected in Langkawi Island, a popular tourism destination in Malaysia and the overall findings revealed that from the human health point of view, fin fish found in the coastal areas of the island are safe for the consumption. The mineral and heavy metal contents are within the allowable limit of consumption.